Title: Symptomatic unruptured pediatric intracranial aneurysm poses a - محفوض, مفيد (Latakia University Journal -Medical Sciences Series, 2023)
Intracranial aneurysms are rare in the pediatric population and constitute less than 2% of all cerebral aneurysms. Relative to their adult counterparts, published series have been few. The proportion of ruptured aneurysms in patients younger than 15 years is less than 1%. The occurrence of aneurysms is probably the result of an interplay between congenital factors and hemodynamic stress. Our case is a 10-year-old boy suddenly presented to the emergency department complained of severe headache, diplopia and partial ptosis. There was no history of systemic upset, trauma or relevant medical or surgical history. Urgent brain CT scan and Brain MRI were performed with normal findings. The patient was admitted to pediatric ICU for ICP monitoring. Standard clinical examination and laboratory investigations were done to exclude intracranial infection, toxins and metabolic conditions. Enhanced CT angiography revealed a 5 mm saccular ICA bifurcation aneurysm on the left side. Detailed screening and imaging were done to rule out any associated conditions, such as Autosomal dominant polycystic kidney disease (ADPKD), fibro muscular dysplasia, coarctation of aorta, Ehlers syndrome, and Marfans syndrome. A multi-disciplinary team (MDT) meeting had been held and surgery was recommended after interdisciplinary decision with radiologist and two neurosurgeons. The patient underwent microsurgical clip ligation of ICA bifurcation aneurysm after 10 days of symptoms. The patient was discharged on day 7 after operation. Post-procedure CTA showed complete exclusion of the aneurysm from the circulation. Conclusion Diagnosis of symptomatic unruptured intracranial aneurysm is challenging. The next challenge is to determine which aneurysms pose a significant risk for future rupture. The management of pediatric intracranial aneurysms is controversial. A multidisciplinary team is best able to treat such complex conditions. Key Words: unruptured aneurysm, pediatric intracranial aneurysm, Surgical clipping